Functional characterization of transient receptor potential (TRP) channel C5 in female murine gonadotropes - Beck, Andreas; Freichel, Marc (Endocrinology, 2017)
We used combinatorial genetic strategies including genetic confocal Ca2+ imaging in whole-mount pituitary gland preparations to characterize TRP channel C5 func
Gesehen am 13.09.2018